Industrial Systems Simulation Applied to Laboratory Practices in the Industrial Engineering Degree - Rivera Rivera, María José; Pascua, Paola (LACCEI, 2024)
Laboratory practices that are carried out in person present difficulties to conclude on time, since the preparation time and reorganization of elements represents a significant amount of class time. To this end, we sought to analyze whether the use of simulation can optimize the time of these laboratories and analyze the effects of its implementation. A simulation model was developed to represent one of the laboratories of the Industrial Engineering degree at UNITEC. Choosing 4 different populations, corresponding to 4 different classes of the degree, which would be used as their own sample.In relation to the parameters of this study, it was concluded that the simulation can be used to develop laboratories for the Industrial and Systems Engineering degree at UNITEC, thus achieving 95.65% completion of the results obtained through the traditional methodology. reducing by 50% the time necessary to complete the laboratory practice. This result can be obtained as long as students have prior knowledge in using the simulator and have adequate guidance throughout the laboratory.Keywords: FlexSim, comparison, educational simulation, traditional education, student performance